DNA barcoding as a valuable tool for delimiting mollusk species of the genus Biomphalaria Preston, 1910 (Gastropoda: Planorbidae) - de Araújo, Amanda Domingues; Carvalho, Omar dos Santos; Gava, Sandra Grossi; Caldeira, Roberta Lima (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The genus Biomphalaria in Brazil includes 11 species and one subspecies, three of which are intermediate hosts of Schistosoma mansoni. Due to the recent evolution of this group, some species are difficult to identify based on morphological characters, making the use of genetic markers necessary for species identification. This study aimed to evaluate the use of partial sequences of the cytochrome c oxidase I (coi) gene for the identification of Biomphalaria species using phylogenetic reconstruction and species delimitation algorithms. The study tested the use of DNA barcoding technique for species delimitation within the genus. Methods DNA barcoding was performed by sequencing a partial region of the coi gene from specimens, and the sequences were analyzed using phylogenetic reconstruction and algorithms to delimit Operational Taxonomic Units (OTUs). Results The study found that the use of the coi gene in the reconstruction of the phylogeny of the genus might be an alternative for understanding the evolution and dispersion of species. However, this marker alone is not enough to solve complex taxonomic problems within the genus. A total of 223 sequences were analyzed, 102 of which could be separated using the barcode gap, enabling the correct identification of seven taxa. Discussion The study demonstrated that accurate mollusk identification is necessary for effective schistosomiasis control. The DNA barcoding methodology was found to be promising for accurate mollusk identification, which is crucial for concentrating schistosomiasis control efforts in places where it is needed.